DIGITAL-BASED ZERO WASTE MANAGEMENT IN JASMINE INTEGRATED FARMING TO IMPROVE COMMUNITY WELFARE - Simatupang, Frido Saritua; Hafidh Nurmansyah, Abdul Ahmad; Yulina, Henly; Maulana, Lucky Hikmat (LPPM Univ. Ibn Khaldun Bogor, 2023)
Jasmine Integrated Farming is a farmer group located in community unit 19, Antapani Tengah Subdistrict, Bandung City. Jasmine Integrated Farming was founded in 2019 with all its problems, namely (1) organic waste processing that is not yet optimal, (2) irregular planting and harvest schedules, (3) catfish harvests are not optimal, (4) lack of understanding about caring for seed houses and nurseries. plants, (5) Lack of partner knowledge about digital marketing, (6) Lack of knowledge about bookkeeping and financial reports. With all its problems, it is difficult for this farmer group to generate profits for the welfare of its members. The solutions offered are training and assistance on organic waste processing, training and assistance on seeding and planting schedules, training and assistance on the use of digital media for promotions along with recording digital-based financial reports using applications. The conclusion of this service is that there is an increase in partners' knowledge about organic waste processing, planting schedules, using social media as a marketing medium and recording application-based financial reports via Buku Kas.